Antioxidant response of Messastrum gracile (Chlorophyceae) to light-induced stress - Tavares, Lúcia Helena Sipaúba [UNESP]; Gratão, Priscila Lupino [UNESP]; Nicolau, Mayara Cristina Malvas [UNESP]; Tedesque, Mayara Galatti [UNESP] (Universidade Estadual de Maringa, 2023)
The antioxidant enzymes activities during the Messastrum gracile growth period under two different light intensities were evaluated. The light intensities were designated as: control at 60 µmol photons m-2 s-1 and two cultivations under light-induced stress at 120 µmol photons m-2 s-1, during 24 and 72 hours. The maximum cell density in all treatments was achieved on the 21st growth day with 140x105 cells mL-1 (control), 382x105 cells mL-1 (24 hours) and 236x105 cells mL-1 (72 hours). The antioxidant enzymes activities were more elevated in the control, however, GSH-Px, CAT and SOD activities were higher on the 7th growth day, while GPOX and GR activities were higher on the 28th and 21st growth day, respectively. The microalgae displayed lower MDA content, which indicates low stress levels. In terms of growth, biomass production and chlorophyll-a, the best results occurred under light-induced stress (120 µmol photons m-2 s-1). Light-induced stress decreased antioxidant activity during M. gracile growth, and the results revealed a higher activity for glutathione peroxidase, catalase and superoxide dismutase.
Keywords: 120 µmol photons m-2s-1; cell growth; CHU12; enzymes activities